Naznake identiteta u hrvatskom i slovenskom putopisu Ivana Macuna - Riman, Kristina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2014)
In the 19th century the modern nations were shaped and the language corpora of individual nations were built. In such an environment, the question of language and national identity appeared among the South Slav peoples, too. Macun was a Slovene reformer who espoused the Illyrian idea of Ljudevit Gaj about the integration of the Slovene and Croatian languages. In this paper we look at two travelogues by Macun that are particularly inspiring for the consideration of questions of the author%s relationship to his own identity. The author reveals himself through comparisons with other identities and cultures that he observes and describes, expressing his image through views on people and space. Another approach to uncover the author%s identity is derived from the application of the theory of reception when considering a work written for the Slovene and Croatian audience. The analysis of his two travelogues leads to the conclusion that Macun was aware of his Slovene identity and he did not equate himself with other South Slav peoples, while he emphasized the importance of their interconnection.
Keywords: Macun, Ivan, 1821-1883; Literarni zgodovinar; literary historian; potopisi; identiteta